2018
DOI: 10.1002/jcu.22595
|View full text |Cite
|
Sign up to set email alerts
|

The inter‐observer agreement in the assessment of carotid plaque neovascularization by contrast‐enhanced ultrasonography: The impact of plaque thickness

Abstract: The interobserver agreement for assessing carotid plaque neovascularization by using contrast-enhanced ultrasonography is substantial and acceptable for research purposes, regardless of the maximal thickness of the plaque.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In the present study, the thickest plaque rather than plaque which caused the recurrence of IS was evaluated. However, previous studies have reported that the stability of the largest plaque is signi cantly related to the occurrence of cerebral infarcts [25,26]. Moreover, the present study was retrospective in nature and whether the conclusions drawn hold the same signi cance in the prospective study needs to be evaluated further.…”
Section: Limitationsmentioning
confidence: 77%
“…In the present study, the thickest plaque rather than plaque which caused the recurrence of IS was evaluated. However, previous studies have reported that the stability of the largest plaque is signi cantly related to the occurrence of cerebral infarcts [25,26]. Moreover, the present study was retrospective in nature and whether the conclusions drawn hold the same signi cance in the prospective study needs to be evaluated further.…”
Section: Limitationsmentioning
confidence: 77%